The Ghastly love of Johnny X [videorecording (DVD)] - Bunnell, Paul, 1963-; Bunnell, Paul, 1963-; Bunnell, Paul, 1963-; Keenan, Will; Brooks, De Anna Joy; Bratton, Creed, 1943-; Harnden, Russell, III (Strand Releasing, 2013)
Banished to Earth for intergalactic juvenile delinquency, Johnny X and his gang of Ghastly Ones set off in search of a piece of alien technology that could change the fate of the universe forever. Soon, the extraterrestrial no-goodniks are embroiled in a wacky scheme involving a femme fatale named Bliss, a shifty concert promoter with schemes of his own, and a recently deceased musician who won't let a little decomposition stop him from rocking.